The Influence of Extrinsic Learning Motivation Toward Physics Learning Outcomes of the Tenth Graders of Jayapura Muhammadiyah SHS During the Covid-19 Pandemic - Azis, Kamasia; Panda, Florentina Maria; Budiarti, Indah Slamet (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2021)
This study aims to determine the relationship, and the influence of extrinsic learning motivation on student learning outcomes. This type of research is ex post research facto. The data collection technique used was a questionnaire. The data obtained were analyzed using the SPSS 16 program. The study population was 61 class X students. The research sample was class X1 with a total sample of 30 students. The analysis technique used was correlation techinique. Research results and data processing asymp value sig (2-tailed) 0,000 < 0,05, meaning that there is a relationship between extrinsic learning motivation and student learning outcomes. The pearson correlation value of 0,934 is interpreted to have a very strong relationship. The value of R Square 0,872 means that the influence of extrinsic learning motivation on learning outcomes is 87,2%. Sig value 0,000 < 0,05 meaning that there is an influence on extrinsic learning motivation learnig outcomes of students.